Kapsul Gravitasi sebagai Media Eksperimen Fisika Sederhana untuk Anak SD di Rumah Singgah - Erwani Merry Sartika; Meilan Jimmy Hasugian; Markus Tanubrata; Novie Theresia Br. Pasaribu; Herawati YS; Arvin Ezekiel Denri Utama; Dido Hardinanto Ginting; Jeffrey Christopher; Yehuda Njuah Sectio Cibro (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2025)
The gravity capsule served as the main object of focus in a community service activity aimed at introducing science to children in the Cibogo Bandung shelter, specifically targeting first and second-grade elementary school students. The service learning method was employed to ensure the learning process remained simple and accessible, considering the young age of the participants. A basic experiment using the gravity capsule was conducted to introduce fundamental science concepts such as gravity, energy, and momentum. The outcome of this community service activity was considered successful, with a comprehension rate of 78.5%, based on responses to questions covering the materials delivered. However, improvements are still needed to enhance content retention among participants. Additionally, requests from the partner community for the program to be conducted regularly form the foundation for the sustainability of this initiative.